Psychodynamic therapy meets evidence-based medicine: a systematic review using updated criteria. (July 2015) - Leichsenring, Falk; Luyten, Patrick; Hilsenroth, Mark J; Abbass, Allan; Barber, Jacques P; Keefe, John R; Leweke, Frank; Rabung, Sven; Steinert, Christiane
Summary Psychodynamic therapy (PDT) is an umbrella concept for treatments that operate on an interpretive-supportive continuum and is frequently used in clinical practice. The use of any form of psychotherapy should be supported by sufficient evidence. Efficacy research has been neglected in PDT for a long time. In this review, we describe methodological requirements for proofs of efficacy and summarise the evidence for use of PDT to treat mental health disorders. After specifying the requirements for superiority, non-inferiority, and equivalence trials, we did a systematic search using the following criteria: randomised controlled trial of PDT; use of treatment manuals or manual-like guidelines; use of reliable and valid measures for diagnosis and outcome; adults treated for specific mental problems. We identified 64 randomised controlled trials that provide evidence for the efficacy of PDT in common mental health disorders. Studies sufficiently powered to test for equivalence to established treatments did not find substantial differences in efficacy. These results were corroborated by several meta-analyses that suggest PDT is as efficacious as treatments established in efficacy. More randomised controlled trials are needed for some mental health disorders such as obsessive-compulsive disorder and post-traumatic stress disorder. Furthermore, more adequately powered equivalence trials are needed.